2021
DOI: 10.1002/app.50824
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and antimicrobial properties of ferulic acid grafted self‐assembled bacterial cellulose‐chitosan membranes

Abstract: Bacterial cellulose (BC) is a biomaterial with many excellent properties, but its application as a food packaging and biomedical material is limited due to its lack of antibacterial properties. In this study, ferulic acid (FA) grafted self-assembled bacterial cellulose-chitosan (BCF) membranes were prepared by soaking BC films in chitosan-ferulic acid (CF) solution to synthesize antibacterial biomaterials. 1 H NMR confirmed that FA grafted onto chitosan successfully. The results of field emission scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…cosmetic formulation. This implementation is an example where amphiphilic hemicellulose-based fatty micelles were synthesized with potential application in drug delivery, food, and cosmetics industries due to long-lasting stability (Shen et al, 2021). As mentioned in section Introduction, the main component of BSG is hemicellulose which accounts for 25% of its total weight and can also be incorporated into the formulation of cosmetic products as the amphiphilic stabilizer.…”
Section: Syringic Acidmentioning
confidence: 99%
“…cosmetic formulation. This implementation is an example where amphiphilic hemicellulose-based fatty micelles were synthesized with potential application in drug delivery, food, and cosmetics industries due to long-lasting stability (Shen et al, 2021). As mentioned in section Introduction, the main component of BSG is hemicellulose which accounts for 25% of its total weight and can also be incorporated into the formulation of cosmetic products as the amphiphilic stabilizer.…”
Section: Syringic Acidmentioning
confidence: 99%
“…Regardless of the preparation method, the composites retain the antimicrobial capacity of Chi, have a more flexible structure than BC alone, and preserve the biodegradability and biocompatibility of both polymers [ 110 , 111 , 112 ]. In recent studies, BC membranes were immersed in Chi and Chi–ferulic acid solution to produce membranes with antimicrobial activity [ 112 , 113 ]. Biophysical studies using spectroscopic, SEM, gravimetric, and other techniques demonstrated that BC-Chi composites can hold more water compared with neat BC.…”
Section: Bc Hybrids and Compositesmentioning
confidence: 99%
“…Therefore, there are many other approaches which use combinations of different formulations together with chitosan to improve its antimicrobial effects. Specifically, for wound dressings, many different formulations and approaches have been applied to improve their antibacterial activity, such as: silver formulations [ 138 , 139 ], zinc oxide [ 140 ], nitric oxide [ 104 ], ferulic acid [ 141 ], etc. Through carboxymethylation and selective oxidation of bacterial cellulose and cross-linking with chitosan, Xie et al produced a cellulose–chitosan wound dressing that inhibited bacterial proliferation and exhibited an 80% wound-healing rate after three weeks.…”
Section: Cellulose–chitosan Functional Biocompositesmentioning
confidence: 99%